Renminbi Exchange Rate: Peg to A Wide Band Currency Basket. Issue 1 (January 2017) - Yu, Yongding; Zhang, Bin; Zhang, Ming
Abstract : Persistent renminbi (RMB) devaluation expectations are one of the greatest threats to China's macroeconomic stability. Market interventions backed by huge foreign exchange reserves and capital controls are not sufficient to eliminate the expectations of devaluation. Creating a market‐based and flexible RMB exchange rate regime holds the key to the elimination of devaluation expectations. The present paper compares the pros and cons of several policy options, and proposes to introduce, as a transition to free floating, a new exchange rate regime pegged to a currency basket with a wide band. The new regime should be able to give the RMB exchange rate enough flexibility to eliminate devaluation expectations as well as prevent excessive overshooting. To ensure a smooth transition, the new regime needs to be supported by controlling cross‐border capital flows.